1988
DOI: 10.1128/iai.56.2.523-528.1988
|View full text |Cite
|
Sign up to set email alerts
|

Role of PCF8775 antigen and its coli surface subcomponents for colonization, disease, and protective immunogenicity of enterotoxigenic Escherichia coli in rabbits

Abstract: The role of the PCF8775 antigen and its antigenic subcomponents, in particular, the coli surface (CS) antigen CS6, as colonization factors and protective antigens was studied in the reversible intestinal tie adult rabbit diarrhea model. This was done by testing the abilities of different mutants which carried one or two of the CS components to colonize the intestine and to induce protective immunity against reinfection with PCF8775positive enterotoxin-producing Escherichia coli. Infection with enterotoxigenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Currently, there is no licensed vaccine for use against ETEC diarrhoea. It has been demonstrated that immunization with CF-expressing ETEC strains induces protective immunity against diarrhoea in animal models and humans (Evans et al 1984;Ahren et al 1986;Svennerholm et al 1988;Oyofo et al 2001). For these reasons, CF should be taken as potential antigens to be included into a vaccine formula.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no licensed vaccine for use against ETEC diarrhoea. It has been demonstrated that immunization with CF-expressing ETEC strains induces protective immunity against diarrhoea in animal models and humans (Evans et al 1984;Ahren et al 1986;Svennerholm et al 1988;Oyofo et al 2001). For these reasons, CF should be taken as potential antigens to be included into a vaccine formula.…”
Section: Discussionmentioning
confidence: 99%
“…Many ETEC strains express only CS6 or coexpress it with coli surface antigens CS4 or CS5 (Gaastra and Svennerholm, 1996;Qadri et al, 2005;Ghosal et al, 2007). For all these strains, CS6 was shown to be essential for intestine colonization (Svennerholm et al, 1988). The role of CS6 in intestinal adherence was demonstrated in vitro using bacteria only expressing CS6 and intestinal cell lines (Tobias et al, 2008;Ghosal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Attached bacteria can then deliver their toxin(s). It has not yet been shown that CS6 is an adhesin for human tissue [4], but a study in rabbits indicated that it is a CF [5]. Furthermore ETEC that produce only CS6 cause diarrhea in humans [3].…”
Section: Introductionmentioning
confidence: 99%